Da paisagem (re)existencial a ideal: avaliação da paisagem do sistema hídrico do riacho Maceió - Medeiros, Maria Paula Arcanjo (2024)
Faced with the accentuated territorial dynamics marked by intense urban occupation and exploitation of ecological systems, increasing the adaptive capacity of nature to the maximum, requires a holistic and integrative vision that must necessarily consider the complexity of the territory and its composition supported by public and environmental policies. urban planning. The Maceió stream, located in the eastern portion of the city of Fortaleza, stands out as a significant urban source, which, over time, has become evident the manifestation of tensions of different natures, covering both spatial, social and environmental spheres. and economic. In this context, the research was developed anchored by the following starting question: can landscape assessment as an instrument for interpreting the territory promote the ecosystemic maintenance of the stream Maceió Water System and contribute to guidelines for adherence to urban projects? From this perspective, the objective of the research was to investigate and analyze the landscape as an instrument of interpretation of the stream Maceió Water System in relation to the proposals of the stream Maceió Park Project, in order to verify which conformities and appropriations of use, categorized by landscape values, were incorporated or not into the official project. This was qualitative, exploratory research with a bibliographical survey and case study, which combined the evaluative approaches of the cultural landscape and the analytical approach of urban public space, consecutively. The theoretical-methodological framework proved to be an important conceptual framework for thinking about and structuring urban policies integrated with territorial and landscape values and related to the community's desires.